Multichannel Airy beam generator simultaneously for linear and circular polarized waves. (March 2023) - Liu, Tonghao; Meng, Yueyu; Wang, Jiafu; Ma, Hua; Li, Weihan; Liu, Chao; Zhu, Ruichao; Zheng, Lin; Tang, Wenxuan; Qu, Shaobo
Graphical abstract: Highlights: The multichannel Airy beam generator can independently generate the Airy beams for circular polarized and linear polarized waves. The multichannel beam focusing for circular polarized and linear polarized waves is realized by combining two multichannel Airy beam generators. The multichannel Airy beam generator is constructed through the antenna theory analysis and the Jones matrix analysis. The generated Airy beams possess the obvious diffraction-free, self-bending and self-healing features in the broad frequency band. The low channel crosstalk ensures the high quality of the Airy beams generated simultaneously in three polarization channels. Abstract: The Airy beam has intrigued long-held research interests and developed various striking applications attributed to the unprecedented diffraction-free, self-bending and self-healing properties. Metasurfaces with superior design freedom and small structure size open a fire-new avenue for generating efficient and broadband Airy beam. Nevertheless, most existing Airy beam generators can only respond to one polarization state of electromagnetic waves and produce the single Airy beam, which immensely limit the serviceability and utilization of the Airy beam generators. Herein, an inspiring strategy of multichannel Airy beam generator based on the multichannel amplitude and phase controlled metasurface is proposed to independently generate the Airy beams for linear polarized waves in 20–24 GHz and orthogonal circular polarized waves in 12–14 GHz and 15–17 GHz. Notably, an appealing paradigm of multichannel beam focusing can be realized by the integrated multichannel Airy beam generator, which possesses strong ability to circumvent the obstacle owing to the self-healing feature of the Airy beam. A proof-of-concept prototype is constructed to verify the feasibility of our methodology, and multitudinous simulations and experiments are in excellent accordance with our theoretical predictions. This novel design of multichannel Airy beam generator will have tremendous application potential in sensing, communication and other multifunctional metadevices.